EMPIRICAL STUDY OF CONTINGENCY TIME BUDGET PRESSURE AND AUDIT QUALITY ON THE WEST SUMATRA REPRESENTATIVES OF THE AUDIT BOARD OF REPUBLIC INDONESIA (BPK) - Handayani, Yofa; Riswan, Riswan; Haninun, Haninun (Program Studi Magister Manajemen, 2024)
According to UU Nomor 15 Tahun 2004, the Examination of National Financial Management and Responsibility falls on the Audit Board of the Republic of Indonesia (BPK). The Audit Board of the Republic of Indonesia (BPK) is guided by the National Financial Audit Standards (SPKN) and regulated by Peraturan BPK Nomor 1 Tahun 2017 in order to guarantee audit quality and inspection results in an attempt to realize better, accountable, transparent, economical, effective, and efficient national financial management. Related to this, the quality of the audit can be influenced by several variables such as the employees' competence, experience, ethic, and independence in addition to time budget pressure. This research aims to find the Contingency Time Budget Pressure and the Audit Quality which is moderated by the usage of information technology as a variable. The object of this research is 47 out of 88 certified inspectors of West Sumatra Representatives of the Audit Board of the Republic of Indonesia. The samples are obtained through calculation with a purposive sampling method to determine which respondents will be selected. The research method for this research is qualitative approach with Partial Least Square (PLS) analysis helped by Smart PLS version 3. The result shows that the Time Budget Pressure variable positively and significantly influences the Audit Quality and Information Technology Usage moderating the relation of Time Budget Pressure with Audit Quality to have a strong and significant relationship.